Using Artificial Intelligence to Enhance Language Acquisition in Educational Settings - Quratulain Anwar; Shahid Ali; Zenab Shabbir; Ali Raza Chhalgri Baloch (Dialogue Social Science Review (DSSR), 2025)
This study explores the role of artificial intelligence (AI) in enhancing language acquisition within educational settings. The focus was given on implication of AI in its capacity to transform traditional pedagogical practices. By reviewing a wide range of AI applications, including adaptive learning platforms, natural language processing tools, and conversational agents. The research identifies both the benefits and challenges of integrating AI into language education. The findings reveal that AI significantly improves learner outcomes through personalized instruction, real-time feedback, and gamified engagement strategies. These strategies collectively foster vocabulary development, grammatical accuracy, and oral fluency. Moreover, AI broadens accessibility by offering flexible and continuous opportunities for independent learning, especially in under-resourced contexts. Despite these advantages, the study highlights pressing concerns related to data privacy, algorithmic bias, and unequal access to technological infrastructure. Teacher readiness also emerges as a crucial factor, as insufficient training can hinder effective implementation. The results suggest that AI must function as a supportive tool rather than a replacement for teachers. The hybrid models produce the most promising outcomes. It is recommended that policymakers and educators adopt AI in ways that ensure ethical safeguards, professional training, and equitable access while fostering collaboration between technology and human instruction. This balanced integration can maximize the transformative potential of AI while preserving the human dimensions of empathy, culture, and critical thinking that remain central to language education.